Athermal jamming vs. glassy dynamics for particles with exponentially decaying repulsive pair interaction potentials with a cutoff - Wohlleben, Nicolas; Schmiedeberg, Michael (EPL - Europhysics Letters, 2021)
We study athermal jamming as well as the thermal glassy dynamics in systems composed of spheres that interact according to repulsive interactions that exponentially decay as a function of distance. As usual, a cutoff is employed in the simulations. While the athermal jamming transition that is determined by trying to remove overlaps is found to depend on the arbitrary and therefore unphysical choice of the cutoff, we do not find any athermal jamming transition or crossover that only relies on the physical decay length. In contrast, the glassy dynamics mainly depends on the decay length. Our findings constitute another demonstration of the fact that the athermal jamming transition is not related to thermal glassy dynamics. In addition, we argue that interactions without sharp physical cutoff should be considered more often as a model system in jamming. The reevaluation of widely used theoretical approaches or methods of analysis in the field of jamming and the task to change them such that they do not depend on unphysical cutoffs will lead to deeper insights into the nature of athermal and thermal jammin
Keywords: Glass transition; Jamming; cutoff; exponential interaction